Community Security Responses to Insecurity in Ondo State, Nigeria: An Assessment of Causes, Effects, and the Role of Amotekun and Other Security Agencies - Olowo, Oluwatoyin Olusegun (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2025)
Insecurity remains a persistent and destabilising challenge in Nigeria, particularly at the grassroots level, where state protection is often inadequate. The growing wave of criminal activities—ranging from kidnapping and robbery to communal clashes—has increasingly prompted local responses to security threats. This study investigates the causes, effects, and strategic responses to insecurity in Akoko North East Local Government Area of Ondo State, Nigeria, with particular attention to the role of community-based security outfits such as the Amotekun Corps. A descriptive survey design was adopted, targeting security personnel across multiple agencies operating within the study area. One hundred (100) respondents were randomly selected, and data were collected using a validated, researcher-designed questionnaire. Descriptive statistics, including frequency counts, mean scores, and percentages, were employed to analyse the findings. Results indicate that the most prevalent security threats include kidnapping, Fulani herdsmen-related violence, and armed robbery. Major causes of insecurity were identified as unemployment, poverty, political corruption, and weak institutional frameworks. The effects of insecurity included displacement, mistrust, and social disintegration. Notably, Amotekun and other local actors were perceived as vital in augmenting conventional law enforcement efforts, particularly through their responsiveness and local intelligence networks. The findings underscore the need for integrating community-based security initiatives into Nigeria’s broader security architecture. Policy reforms should focus on strengthening local capacity, improving inter-agency collaboration, and addressing the structural roots of insecurity